COMMUNITY DEVELOPMENT-BASED ISLAMIC EDUCATION PARADIGM (CBE): IMPLEMENTATION STUDY AND ITS IMPACT ON LOCAL EMPOWERMENT AT AL MUNAWIR PESANTREN PESANTREN SANGATTA, EAST KUTAI - Rusini, Rusini; Zamroni, Zamroni; Tamam, Badrut (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The Community-Based Education (CBE) paradigm in Islamic education emphasizes the active involvement of local communities in the educational process to achieve broader social and economic empowerment. This study explores the implementation and impact of CBE-based Islamic education at Pesantren Al Munawir in Sangatta, Kutai Timur. The research aims to understand how this educational model fosters local empowerment and enhances community participation in both educational and socio-economic spheres. By examining the strategies, activities, and outcomes of the pesantren's CBE initiatives, this study highlights the significant role of Islamic education in shaping local development and providing sustainable solutions for the community's needs